I rischi naturali del cambiamento climatico nelle città del Mediterraneo - Guida, Carmen (Smart City, Urban Planning for a Sustainable Future, 2021)
Cities across the planet are seriously threatened by the impacts of climate change. Hence,effective and efficient strategies are required to reduce their exposure and vulnerability in order to prevent potential harmful damage to the population. Cities in climate sensitive zones would pay a high price, just like those bordering the Mediterranean, which are the focus of this work. This volume is structured in four parts. In the first, the cultural, political and scientific frame of the theme of climate change is presented, through an excursus of the negotiations, agreements and scientific advances that have divided the opinion of researchers, citizens and policymakers. The second section deals with the theme of risk theories and their application to the governance of urban and territorial transformations. The third presents a focus on the Mediterranean and the network of cities located along its coasts. In the last part, the extreme climatic events that have the highest probability of occurring for the Mediterranean area are explored.